A Phase 1 dose escalating study of double mutant heat-labile toxin LTR192G/L211A (dmLT) from Enterotoxigenic Escherichia coli (ETEC) by sublingual or oral immunization. Issue 4 (21st January 2019) - Bernstein, David I.; Pasetti, Marcela F.; Brady, Rebecca; Buskirk, Amanda D.; Wahid, Rezwanul; Dickey, Michelle; Cohen, Mitchell; Baughman, Holly; El-Khorazaty, Jill; Maier, Nicole; Sztein, Marcelo B.; Baqar, Shahida; et al.
Highlights: This dose escalating clinical trial showed that the dmLT formulation was safe. The formulation was only moderately immunogenic at doses up to 50 µg. Antibody titers following oral administration were higher than after SL dosing. Abstract: Background: The public health burden of Enterotoxigenic Escherichia coli (ETEC) is high but no vaccine is specifically approved to prevent ETEC infections. Methods: We performed a Phase 1, dose escalation study (1–50 µg) evaluating the sublingual (SL) delivery of the double mutant heat-labile toxin LTR192G/L211A (dmLT) in 80 healthy adult volunteers. The primary objective was safety and the secondary was the immunogenicity of the dmLT. Subjects received 3 doses of dmLT at days 1, 15, and 29. Subjects receiving the first dose at each dosage level were observed overnight in a research facility. The second and third doses were administered on an outpatient basis. Data from cohorts 1–4 were used to select the cohort 5 dose (25 µg), comparing SL and oral routes. Results: The vaccine appeared safe and well tolerated with only rare development of vomiting or diarrhea. The serum anti-dmLT IgA and IgG and neutralizing antibody responses were modest after any of the SL immunizations. Serum IgA and IgG titers were increased at the higher antigen doses (25 or 50 µg) but the percent with 4-fold increases was at best 38% for both IgA and IgG. The 4-fold increase among subjects receiving all 3 doses was 43% for both IgA and IgG. Antibody titers following oral administration were, in general, significantly higher than after SL. The frequency of IgA- or IgG-ASCs in circulation were somewhat vaccine dose dependent and were detected at a moderate level. However, antibodies in saliva or stool were rarely detected. Post-vaccination increases in T cells or cytokine production were also infrequent. Conclusion: The dmLT vaccine formulation evaluated here was safe but only moderately immunogenic at doses up to 50 µg when administered by the SL or oral route. Studies at higher doses with better formulations appear warranted.